The drag queen anthology : the absolutely fabulous but flawlessly customary world of female impersonators - Schacht, Steven P.; Underwood, Lisa (Harrington Park Press, 2004)
Examine the cultural and political implications of male-to-female gender performance! The Drag Queen Anthology: The Absolutely Fabulous but Flawlessly Customary World of Female Impersonators examines the phenomena of male-to-female gender performance and the people who live it. This provocative collection of original essays explores the possibilities, limitations, ironies, and controversies surrounding men who perform as women to an audience that knows the truth but celebrates the illusion. The book's contributors call on extensive backgrounds in sociology, anthropology, theater, liter.